1981
DOI: 10.1111/j.1744-6570.1981.tb00490.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of a Trait‐oriented Job Analysis Technique

Abstract: A trait‐oriented job analysis technique based on a checklist of 33 a priori carefully defined traits that encompass elements of the physical, mental, learned, motivational and social domains of the work world is described. The analysis identifies the relevant traits, their levels and weights, in relation to overall job performance. Results of discriminability tests were supportive of the job analysis technique and indicated that incumbents of jobs requiring a particular trait scored higher on measures (predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Foti & Lord, 1987;Lord et al, 1982). This instrument contains traits relevant to a large range of occupations, including those requiring leadership skills (Lopez, Kesselman, & Lopez, 1981). Interrater agreement in the traits selected as relevant to performance meet professional standards (F. Lopez et al, 1981).…”
Section: Task-specific Self-esteemmentioning
confidence: 99%
“…Foti & Lord, 1987;Lord et al, 1982). This instrument contains traits relevant to a large range of occupations, including those requiring leadership skills (Lopez, Kesselman, & Lopez, 1981). Interrater agreement in the traits selected as relevant to performance meet professional standards (F. Lopez et al, 1981).…”
Section: Task-specific Self-esteemmentioning
confidence: 99%
“…This fundamental distinction between JA versus JS was re¯ected in the de®nition of JA oered by Harvey (1991, p. 74), which explicitly excluded speculations regarding`job requirements' that are couched in terms of inferred worker KS requirements and hypothetical AO traits. Unfortunately, some authors persist in choosing to blur this distinction by using the term`job analysis' to refer to both the description of work, as well as the process of inferring worker-trait requirements,`competencies,' and similar speculative judgments (e.g., Fleishman and Mumford, 1991;Hughes and Prien, 1988;Lopez, Kesselman and Lopez, 1981). Numerous reasons exist for arguing against this practice (see Harvey, 1991, pp. 75±78 for a more detailed discussion), including the types and magnitudes of inferences required, the cognitive decision making processes involved, the amounts and levels of speci®city of information that must be considered, and perhaps most important, the fundamental dierences in the types of properties being rated (i.e., properties of jobs, expressed in terms of work behaviors and contextual characteristics, in the case of job analysis, versus properties of people, expressed in terms of hypothetical psychological traits, in the case of job speci®cation).…”
Section: Speci®c Points Of Contentionmentioning
confidence: 99%
“…Previous research has shown that job analyses help to accurately identify the personality traits that are job relevant, and thus enhances personality test validity via first identifying those personality traits that are content valid (Levine, Ash, & Bennett, 1980;Lopez, Kesselman, & Lopez, 1981;Tett et al, 1991). Thus, an extensive job analysis was performed for the present study on the bank teller job class for which the organization was enhancing its human resource selection process.…”
Section: Job Analysismentioning
confidence: 99%